2010 IEEE/RSJ International Conference on Intelligent Robots and Systems 2010
DOI: 10.1109/iros.2010.5650701
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal modeling of grasping actions

Abstract: Abstract-Understanding the spatial dimensionality and temporal context of human hand actions can provide representations for programming grasping actions in robots and inspire design of new robotic and prosthetic hands. The natural representation of human hand motion has high dimensionality. For specific activities such as handling and grasping of objects, the commonly observed hand motions lie on a lower-dimensional non-linear manifold in hand posture space. Although full body human motion is well studied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…An alternative representation of hand posture compatible with soft hand mechanics has been used for the Human Grasp Database 3 experiment. In this experiment, Romero et al (2010) represented hand posture in terms of fingertip position and orientation relative to the back of the hand.…”
Section: Choice Of Representationmentioning
confidence: 99%
“…An alternative representation of hand posture compatible with soft hand mechanics has been used for the Human Grasp Database 3 experiment. In this experiment, Romero et al (2010) represented hand posture in terms of fingertip position and orientation relative to the back of the hand.…”
Section: Choice Of Representationmentioning
confidence: 99%
“…The correlations are not obvious and cannot be modeled explicitly; therefore, data-driven approaches are commonly used to determine the coupling between them. Thus, only a few parameters suffice to define a hand posture [9] or hand movement [10]- [12]. The minimum number of parameters required to specify the posture of the hand is called the intrinsic dimension of the hand or the number of DoF of a hand.…”
Section: Related Workmentioning
confidence: 99%
“…We have previously shown that using the GP-LVM model, a 2-D space is sufficient to encode the variations in this data. To this end, we use a 2-D latent representation [12]. In addition this is beneficial as it provides simple means of generating intuitive visualizations.…”
Section: Low-dimensional Spacementioning
confidence: 99%
“…Similarly, one can consider the space of continuously varying hand configurations. A successful technique is to represent robot hand configurations as elements of a vector space and to employ principal component analysis to determine postural synergies [8,18]. These then define a low-dimensional representation which can be used to control a robotic hand.…”
Section: Background and Related Workmentioning
confidence: 99%